Case Report: Transformation of natural killer-cell large granular lymphocytic leukemia to aggressive natural killer cell leukemia - Wang, Wen; Lu, Ke; Xing, Lijie; Li, Zengjun (Frontiers in Oncology, 2025)
Large Granular Lymphocytic Leukemia (LGLL) is a rare clonal proliferative disorder of cytotoxic T lymphocytes (CTL) and natural killer (NK) cells, characterized by persistent expansion of large granular lymphocytes (LGLs) in peripheral blood for over six months. According to the 2022 World Health Organization (WHO) classification, LGLL is categorized into T-LGLL, NK-large granular lymphocytic leukemia (NK-LGLL). Aggressive natural killer cell leukemia (ANKL), as a Mature T-cell and NK-cell leukemia independent of LGLL, also has morphologic characteristics of large granular lymphocytes. This report describes a rare case of NK-LGLL transforming into ANKL. This case highlights the necessity of differential diagnosis in LGLL and suggests that proteasome inhibitors combined with immune checkpoint inhibitors may represent a promising therapeutic strategy for ANKL.